Michel Foucault and Antipsychiatry: Psychiatric Power in Perspective - Chamorro, Emmanuel; Ferraro, José Luís (BioLaw Journal - Rivista di BioDiritto, 2024)
This paper examines the connection between Michel Foucault and antipsychiatry, taking his 1973–1974 lectures Psychiatric Power as a starting point. Our analysis begins by observing how the problem of madness reemerges in Foucault’s work both because of its affinity to the currents critical of psychiatry and the transformations of the French intellectual field at the time. From this situated perspective, Psychiatric Power becomes particularly relevant because it allows us to connect the three fundamental problems of all Foucauldian work—knowledge, power, subjectivity—around the critical analysis of the modern political technologies.